VL-HIV co-infection with Leishmania containing skin lesions resembling para-kala-azar dermal leishmaniasis. - Natália O Alves; Jéssica A Oshiro; Yunna C Silva; Gabriela C Pacher; Aline E Casaril; Yasmin S Rizk; Silvia N O Uehara; Anamaria M M Paniago; Isadora L X Andrade; Carla C P Arruda; Alessandra G Oliveira (Public Library of Science (PLoS), 2024)
Leishmaniases are a group of neglected vector-borne infectious diseases that are among the six priority endemic diseases worldwide. Visceral leishmaniasis (VL) is the most severe clinical manifestation, characterized by systemic and chronic visceral involvement and high mortality in immunosuppressed and untreated patients. VL can be complicated into post-kala-azar dermal leishmaniasis (PKDL), and when dermatologic disorders occur simultaneously with active VL, an intermediate clinical form called para-kala-azar dermal leishmaniasis (para-KDL) occurs. This clinical form is of great epidemiological relevance, as humans act as a source of infection for vectorial transmission. In the Americas, Brazil is among the seven countries responsible for more than 90% of VL cases, though reports of PKDL and para-KDL are rare. This paper presents three cases of VL-HIV co-infection with Leishmania-containing skin lesions resembling para-kala-azar dermal leishmaniasis. The cases were investigated by the team from the Infectious Diseases Department of University Hospital (HUMAP/UFMS) in Mato Grosso do Sul, Brazil. The three patients exhibited skin lesions where amastigote forms of L. (L.) infantum were identified. All cases exhibited similar clinical manifestations of para-KDL, including fever, hepatosplenomegaly, pancytopenia, and disseminated skin lesions. The study described the prevalence of comorbidities, the incidence of VL relapse, and the therapeutic regimen in relation to the outcomes. The study underscores the importance of follow-up and secondary prophylaxis in patients with VL, which are essential for the efficacy of the treatment. Furthermore, the study provides insight into the potential epidemiological profile of para-KDL cases in Brazil, which contributes to the development of more efficient clinical management strategies for patients.